Effectiveness of the Regional Government Information System (SIPD) in the Preparation of Financial Reports: Evidence from Aceh Tamiang Regency - Desyana Putri; Ulfa Utari (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the effectiveness of the Regional Government Information System (SIPD) application in supporting the preparation of Local Government Financial Reports (LKPD) in Aceh Tamiang Regency. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and document studies. The results show that SIPD has been effectively used in integrated regional financial management, as evidenced by the achievement of an Unqualified Opinion (WTP) Opinion from the Badan Pemeriksa Keuangan Republik Indonesia (BPK-RI) for three consecutive years (2022–2024). However, technical and human resource constraints still need to be optimized. SIPD effectiveness is supported by government commitment, system integration, and human resource capacity building. This study recommends enhancing technical training and continuous assistance for regional financial management officials.